Quitline Queensland: the journey to a globally unique smoking cessation service in Australia - Isbel, Joanne; Kennedy, Madonna; West, Mark; O’Grady, Kerry-Ann F.; Peardon-Freeman, Shelley (Frontiers in Public Health, 2025)
Smoking cessation programs remain a core component of global efforts to reduce smoking and nicotine addiction. Telephone-based counselling, with or without the provision of nicotine replacement therapy, commonly referred to as Quitlines, has been a cornerstone of smoking cessation programs and they vary in scope and content and the populations they target. We describe the history, and structure of Quitline Queensland, Australia that was implemented in 1997. Quitline Queensland offers intensive quit support programs incorporating 4 weeks of telephone-based counselling, free nicotine replacement therapy mailed to participants and up to 12 months of follow-up. The program has evolved through a strong government commitment to, and support for, evidence-based solutions to reducing the burden of smoking in Queensland. Eligible cohorts have been identified by evidence-based reviews, equity considerations, trends in smoking prevalence and to address new challenges to smoking cessation such as vaping and the impact of the COVID-19 pandemic. New approaches to engaging and retaining smokers and delivering the program are being evaluated and implemented.